Dynamometer and Instrumentation for Determining Electric Motor Power, Efficiency, and Power Factor - Johnson, Donald M. (Journal of Agricultural Systems, Technology, and Management, 2002)
Alternating current (AC) electric motors are widely used in the agricultural industry, yet many students do not understand their basic operating characteristics. Welldesigned laboratory activities can provide an excellent method for students to observe and actively study motor operation. However, commercially available electric motor dynamometers are prohibitively expensive for many agricultural systems technology programs at both the secondary and university levels. This article describes the construction and evaluation of an inexpensive “spring-and-string” electric motor dynamometer that allows students to actively study the power output, efficiency, and power factor of small, fractional horsepower AC electric motors. The necessary instrumentation is also described. The dynamometer and instrumentation produced consistent results when used to test a 1/20-hp electric motor.